PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN PADA BALAI TAMAN NASIONAL KEPULAUAN SERIBU - Tyas Alifa Ardayanti (2021)
Library is a source of information that is accessible for most people. With the rapid development of the existing technology, it is possible for each individual to create such an innovation or ideas that can simplify their work daily. By utilizing available websites with internet access, the making of digital library systems is one efficient solution for their organization's publication tools. Balai Taman Nasional Kepulauan Seribu is one of governmental institutions that still use library in conventional way in managing their data and publication of their collection, therefore in this study the author aims to design a website-based library information system that facilitates the management of books data and research publication and library information systems publication tools so that information can be more accessible and could reach wider community.